Exogenous plant hormones and cyclotide expression in Viola uliginosa (Violaceae). (September 2015) - Slazak, Blazej; Jacobsson, Erik; Kuta, Elżbieta; Göransson, Ulf
Graphical abstract: The regulation of cyclotide expression is related to plant hormones governing tissue development. The production of cyclotides can be controlled in vitro . Highlights: 20 cyclotide sequences, including 12 new were found in V. uliginosa . Cyclotide expression can be controlled in vitro . Regulation of cyclotide expression is related to plant hormones governing tissue development. High cyclotide yielding suspension culture was obtained. Abstract: Plants from Violaceae produce cyclotides, peptides characterized by a circular peptide backbone and a cystine knot. This signature motif gives stability that can harness a wide spectrum of biological activities, with implications in plant defense and with applications in medicine and biotechnology. In the current work, cyclotide expressing in vitro cultures were established from Viola uliginosa . These cultures are useful models for studying biosynthesis of cyclotides and can also be used in their production. The cyclotide expression pattern is shown to be dependent on exogenous plant growth regulators, both on peptide and gene expression levels. The highest yields of cyclotides were obtained on media containing only a cytokinin and were correlated with storage material accumulation. Exposure to auxins decreased cyclotide production and caused shifting of the biosynthesis pattern to root specific cyclotides. The response to stimuli in terms of cyclotide expression pattern appears to be developmental, and related to polar auxin transportation and the auxin/cytokinin ratio regulating tissue differentiation. By the use of whole transcriptome shotgun sequencing (WTSS) and peptidomics, 20 cyclotide sequences from V. uliginosa (including 12 new) and 12 complete precursor proteins could be identified. The most abundant cyclotides were cycloviolacin O3 (CyO3), CyO8 and CyO13. A suspension culture was obtained that grew exponentially with a doubling time of approximately 3 days. After ten days of growth, the culture provided a yield of more than 4 mg CyO13 per gram dry mass.